Handbook of Writing, Literacies, and Education in Digital Cultures - Mills, Kathy Ann; Stornaiuolo, Amy; Smith, Anna; Zacher Pandya, Jessica (Taylor & Francis, 2017)
At the forefront of current digital literacy studies in education, this Handbook uniquely systematizes emerging interdisciplinary themes, new knowledge, and insightful theoretical contributions to the field. The chapter topics identified through academic conference networks, rigorous analysis, and database searches of trending themes are organized in five thematic sections: Digital Futures; Digital Diversity; Digital Lives; Digital Spaces; Digital Ethics. This essential guide to digital writing and literacies research, with transformational ideas for educational and professional practice, will enable researchers to position their studies in the field and to generate new themes of inquiry.